RELIGION THAT LEADS TO COMMUNALISM IN POLITICS - Fernando, Antony (Journal of Dharma, 2000)
Religion is a subject of such strange interest to people that it is difficuH to say how many thousands of weeklies, monthlies and quarterlies dedicated solely to the subject of religion come out regularly. In Christianity that number is likely larger than in other religions. However large the number of contemporary religious magazines be, we have also to admit that publications which are mature enough to examine their own religion with a scientific objectivity and look at other religious traditions with respect and without bias are rare. They would not be more than a handful. Of the few open-minded periodicals I have come across, the one I have always looked up to as a model is the Journal of Dharma published by the Dharma Research Association of the Dharmaram College, Bangalore.